2009
DOI: 10.1021/jp810193b
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structure and Interaction Analysis for Supercritical Carbon Dioxide−Ethanol Mixtures: A Monte Carlo Simulation Study

Abstract: Configurational-bias Monte Carlo simulations in the isobaric-isothermal ensemble using the TraPPE-UA force field were performed to study the microscopic structures and molecular interactions of mixtures containing supercritical carbon dioxide (scCO(2)) and ethanol (EtOH). The binary vapor-liquid coexisting curves were calculated at 298.17, 333.2, and 353.2 K and are in excellent agreement with experimental results. For the first time, three important interactions, i.e., EtOH-EtOH hydrogen bonding, EtOH-CO(2) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
3
24
1
Order By: Relevance
“…18 Furthermore, the local environment redistribution dynamics revealed that the time dependent redistribution of the first solvation shell of ethanol is much slower in comparison with the first shell of CO 2 and this observation has been interpreted in terms of the existence of weaker interactions between the CO 2 -CO 2 and EtOH-CO 2 molecules in comparison with the EtOH-EtOH ones, which could be a result of stronger hydrogen bonding ͑HB͒ interactions. Moreover, another recent Monte Carlo simulation study 37 has revealed that the EtOH-EtOH HB network is the most im-portant in these mixtures, having as a result the appearance of aggregates between the EtOH molecules in the fluid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Furthermore, the local environment redistribution dynamics revealed that the time dependent redistribution of the first solvation shell of ethanol is much slower in comparison with the first shell of CO 2 and this observation has been interpreted in terms of the existence of weaker interactions between the CO 2 -CO 2 and EtOH-CO 2 molecules in comparison with the EtOH-EtOH ones, which could be a result of stronger hydrogen bonding ͑HB͒ interactions. Moreover, another recent Monte Carlo simulation study 37 has revealed that the EtOH-EtOH HB network is the most im-portant in these mixtures, having as a result the appearance of aggregates between the EtOH molecules in the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Although a small number of experimental and theoretical studies devoted to the properties of sc CO 2 -methanol mixed solvents ͑with X methanol ϳ 0.01-0.11͒ have been reported up to now, [18][19][20][21][22][23][24][25][26][27][28][29] studies on the properties of scCO 2 -ethanol ͑EtOH͒ systems are quite rare and most of them correspond mainly to dilute mixtures. 24,[30][31][32][33][34][35][36][37] In a quite recent study, two of the authors presented a molecular dynamics ͑MD͒ simulation study on the local intermolecular structure and related dynamics for the sc CO 2 -EtOH binary mixture at a mole fraction X ethanol ϳ 0.1. 36 The results obtained in that study have revealed a nonideal mixing behavior of the mixture and the existence of a somewhat restricted aggregation between the ethanol molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to computer simulations, they are very useful for investigating dynamic, structural and thermodynamic properties, allowing researchers to complement other existing studies and get valuable information not directly obtained by experiment [21,[27][28][29] as, for instance, radial distribution functions, coordination numbers, and energetic data.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular simulation has previously been applied successfully to determine solubility of naphthalene, benzoic acid, hydroxybenzoic acid, etc. in ScCO 2 [22][23][24][25]. Here, we attempt to study the thermodynamic properties in solution mixtures of thiophene and ScCO 2 and provide molecular level insights on the interactions between the thiophene and CO 2 in supercritical phase.…”
Section: Introductionmentioning
confidence: 99%